2015
DOI: 10.3109/1354750x.2015.1068862
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate biomarker mass (m/z) ranges in serous ovarian adenocarcinoma using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry profiling

Abstract: Spectral profiles can differentiate plasma samples of ovarian cancer patients from healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Complement C3, inter-alpha-trypsin inhibitor heavy chain H4 and transthyretin were also identified using a combination of carrier protein-bound affinity enrichment strategy with MALDI-TOF MS to characterize OC samples, which is in agreement with our findings [24]. Unfortunately, other OC studies based on MALDI-TOF MS profiling lack the identification step [25, 26]. It is unknown whether other depletion methods are capable of detecting relevant proteins.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Complement C3, inter-alpha-trypsin inhibitor heavy chain H4 and transthyretin were also identified using a combination of carrier protein-bound affinity enrichment strategy with MALDI-TOF MS to characterize OC samples, which is in agreement with our findings [24]. Unfortunately, other OC studies based on MALDI-TOF MS profiling lack the identification step [25, 26]. It is unknown whether other depletion methods are capable of detecting relevant proteins.…”
Section: Discussionsupporting
confidence: 84%
“…In the literature, there are several studies focusing on plasma and serum proteomic patterns of ovarian cancer obtained by MALDI-TOF MS. In order to detect low abundance proteins and peptides, biomarker enrichment kits [24], immunodepletion [25] and magnetic beads [26] have been applied in OC studies. Due to significant impact of sample pretreatment on the MS spectra, the discriminative peaks proposed as candidates for OC biomarkers depend on efficiency of the enrichment strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choosing the right type of MB enables the highest acquisition of proteins and peptides for the furthur proteomic profiling analysis, therfore we compared the performance of two MB and we found that MB-HIC8 had better average peak numbers, higher peak intensitites, and better capturing ability than MB-WCX. HIC showed good performance in previous studies such as the work by (Villanueva et al, 2004;De Noo et al, 2006;Periyasamy et al, 2015) as well as good reproducability (Baumann et al, 2005).…”
Section: Discussionmentioning
confidence: 70%
“…Few studies reported peak identification lists for serum (Villanueva et al, 2006;Tiss et al, 2010) or plasma (Koomen et al, 2005) and this showed the inherent difference between the two type of samples in the moderate percent of concordance in the identified peaks. Several proteomic based studies used plasma (Periyasamy et al, 2015;Baralla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%